The Effects of Engeletin on Insulin Resistance Induced in Human HepG2 Liver Cells - Erdem Toktay; Secil Nazife Parlak; Tugba Kavas; Harun Un; Rustem Anıl Ugan; Muhammed Yayla (Current Issues in Molecular Biology)
In this study, we aimed to investigate the effect of Engeletin (ENG) on insulin resistance and the associated oxidative cell damage in human HepG2 liver cells. The cells were grown in a cell culture medium, and insulin resistance was induced. After the determination of the toxic and effective doses of Engeletin, the effects of Engeletin on insulin resistance and insulin resistance-induced oxidative damage, inflammation, and apoptosis. To induce IR, culture plates were treated with 30 mM glucose and 50 nM insulin and incubated for 48 h. Engeletin and metformin were given one hour before starting the insulin resistance induction. In the HepG2 cells, insulin resistance decreased glucose consumption, the expression of ISR-1 and ISR-2, and the GLUT-2 levels, while they were all increased by Engeletin, which showed a metformin-like effect. In addition, Engeletin alleviated oxidative cell damage by decreasing MDA levels, which increased due to insulin resistance-induced oxidative stress, increasing the GSH and SOD levels and decreasing the caspase-3 (Cas-3), caspase-9 (Cas-9), and tumor necrosis factor alpha (TNF-α) levels, which also increase under insulin resistance conditions. Engeletin was found to have the protective and therapeutic effect of reducing insulin resistance (IR) and the oxidative cell damage it causes in human HepG2 cells.